HUMAN DIGNITY, FIRST-ORDER FACTOR OF HUMAN PERSONALITY (Journal of Teleological Science, 2024)
The most complex being, man, is defined by an understanding of his dignity. Nothing is  more important to humanity than ensuring that dignity is respected. It is dignity that makes man 'truly  human', allowing him to manifest himself in complete freedom and express, unhindered, all the  capacities and abilities with which he has been endowed or which he has developed. This paper explores  various trends in the definition of human dignity and personality, while also examining the concerns of  both ancient Greco-Roman and contemporary societies regarding the implementation of guarantees for  human dignity in the social sphere, legal system, and interpersonal relationships. Although the  exploration is limited, it aims to keep the concept of respect for human dignity at the forefront. This  focus is essential, as the world can only be envisioned as a better place when human dignity is respected.
Keywords: Human dignity; Human being; Christian theology; Existence